Fundamentals of mass spectrometry - Hiraoka, Kenzo (Springer New York, 2013)
Most research and all publications in mass spectrometry address either applications or practical questions of procedure. This book, in contrast, discusses   the fundamentals of mass spectrometry. Since these basics (physics, chemistry, kinetics, and thermodynamics) were worked out in the 20th century, they are rarely addressed nowadays and young scientists have no opportunity to learn them. This book reviews a number of useful methods in mass spectrometry and explains not only the details of the methods but the theoretical underpinning.